CURCUMIN INDUCES APOPTOSIS THROUGH MITOCHONDRIAL-MEDIATED APOPTOTIC PATHWAY IN RETINOBLASTOMA CELLS - SEETHALAKSHMI SREENIVASAN; MS.KARTHIYAINI THIRUMALAI; DR. SUBRAMANIAN KRISHNAKUMAR (International Journal of Pharma and Bio Sciences, 2013)
Curcumin (diferuloylmethane), the main yellow bioactive component of turmeric has been shown to have wide variety of biological actions like anti-inflammatory, anticancer and antioxidant properties. Its anticancer effect is mainly mediated through induction of apoptosis. In the present study, we have investigated the effects of curcumin on growth and apoptosis in the human retinoblastoma (RB) cell line by MTT assay, fluorescence microscopy, flow cytometry and western blotting. Exposure of human RB cells to curcumin inhibited the growth of cell proliferation and resulted in the induction of apoptotic cell death. We also found loss in the mitochondrial membrane potential on curcumin treated cells in a time dependent manner. A decrease in the expression of anti-apoptotic protein and an increase in pro-apoptotic protein were observed after exposure to curcumin. Curcumin also induced the release of cytochrome c and the activation of caspase 3 and 9 was observed in a dose-dependent manner. Thus, these results suggest that the induction of apoptosis by curcumin involves mitochondrial-mediated cell death pathway in human RB cells.